2007
DOI: 10.1007/s00125-006-0543-6
|View full text |Cite
|
Sign up to set email alerts
|

Phenotype-specific inhibition of the vascular smooth muscle cell cycle by high glucose treatment

Abstract: Aims/hypothesis Diabetes accelerates the development of atherosclerosis, which critically involves the proliferation of vascular smooth muscle cells (SMCs). However, how high glucose treatment regulates SMC proliferation is controversial. Considering the established SMC heterogeneity, we hypothesised that glucose treatment may have distinct effects on proliferation of the various phenotypic SMCs. Materials and methods We tested this possibility using cloned spindle-shaped and epithelioid SMCs and laser scannin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 52 publications
1
9
0
Order By: Relevance
“…Western blot analysis was performed as described previously 26. Briefly, protein was extracted from cells with RIPA buffer and equal amounts of protein from each sample (20 μg) were separated by 9% SDS-PAGE and transferred to nitrocellulose membranes.…”
Section: Methodsmentioning
confidence: 99%
“…Western blot analysis was performed as described previously 26. Briefly, protein was extracted from cells with RIPA buffer and equal amounts of protein from each sample (20 μg) were separated by 9% SDS-PAGE and transferred to nitrocellulose membranes.…”
Section: Methodsmentioning
confidence: 99%
“…55,56 Vascular smooth muscle cells (VSMC) undergo phenotypic switching from a quiescent, contractile state to an activated, proliferative, migratory, dedifferentiated state in the setting of hyperglycemia. 57 High glucose concentrations lead to macrophage inflammation and enhancement of response to inflammation, 58 and even transient hyperglycemia leads to epigenetic changes with activation of the nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB) pathway that persists even after return to normoglycemia. 59 Under experimental conditions to simulate glycemic variability in individuals with diabetes, 6 hours of hyperglycemia alternating with normoglycemia within a 24 hour period promotes worsening of endothelial function and increased oxidative stress as compared with continuous hyperglycemia even at serum glucose concentrations as high as 282 mg/dL (15.6 mmol/L).…”
Section: Mechanisms Of Increased Ascvd Risk and Mortality In Type 2 Dmentioning
confidence: 99%
“…Interestingly, Peiro et al (2001) and Zheng et al (2007) reported contradictory results that high glucose inhibited SMC proliferation (Peiro et al, 2001; Zheng et al, 2007). Varma et al (2005) reported that hyperglycemic concentrations of 20 mM and 40 mM glucose significantly decreased human umbilical vein endothelial cell (HUVEC) proliferation compared to 5 mM glucose media(Varma et al, 2005).…”
Section: Introductionmentioning
confidence: 99%